2022
DOI: 10.3389/fbioe.2022.895414
|View full text |Cite
|
Sign up to set email alerts
|

Endophytes in Lignin Valorization: A Novel Approach

Abstract: Lignin, one of the essential components of lignocellulosic biomass, comprises an abundant renewable aromatic resource on the planet earth. Although 15%––40% of lignocellulose pertains to lignin, its annual valorization rate is less than 2% which raises the concern to harness and/or develop effective technologies for its valorization. The basic hindrance lies in the structural heterogeneity, complexity, and stability of lignin that collectively makes it difficult to depolymerize and yield common products. Recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 278 publications
(304 reference statements)
0
1
0
Order By: Relevance
“…In addition, Tony et al (2009) [51] reported that the consortia of microbes were capable of complete mineralization of azo dyes. However, endophytes harboring lignin-degrading activities might be presented with an opportunity to penetrate plants, forming symbionts [52]. An endophyte, which produces cellulase, protease, chitinase, and gelatinase, can hydrolyze fungal cell walls, and can inhibit the adhesion of fungal spores to plants, will have an advantage in mitigating fungal infection and be able to serve as a bio-fungicide.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Tony et al (2009) [51] reported that the consortia of microbes were capable of complete mineralization of azo dyes. However, endophytes harboring lignin-degrading activities might be presented with an opportunity to penetrate plants, forming symbionts [52]. An endophyte, which produces cellulase, protease, chitinase, and gelatinase, can hydrolyze fungal cell walls, and can inhibit the adhesion of fungal spores to plants, will have an advantage in mitigating fungal infection and be able to serve as a bio-fungicide.…”
Section: Discussionmentioning
confidence: 99%